Corrosive effects of fluoride on titanium Investigation by X-ray photoelectron spectroscopy, atomic force microscopy, and human epithelial cell culturing - Stájer Anette; Ungvári Krisztina; Pelsőczi-Kovács István; Polyánka Hilda; Oszkó Albert Zoltán; Mihalik Erzsébet; Rakonczay Zoltán; Radnai Márta; Kemény Lajos; Fazekas András; Laczkóné Turzó Kinga Mónika (2008)
High fluoride (F-) concentrations and acidic pH impair the corrosion resistance of titanium (Ti). Effects of F--containing caries-preventive prophylactic rinses, and gels on Ti were investigated by X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). Human epithelial cell attachment and proliferation were investigated by dimethylthiazol-diphenyl tetrazolium bromide (MTT) and protein content assays. Aqueous 1% NaF solution (3800 ppm F-, pH 4.5) or high (12,500 ppm) F- content gel (pH 4.8) strongly corroded the surface and modified its composition. XPS revealed formation of a strongly bound F--containing complex (Na2TiF6). AFM indicated an increase in roughness (R-a) of the Surfaces: 10-fold for the NaF solution and smaller for the gel or a mouthwash (250 ppm F-, PH 4.4). MTT revealed that cell attachment was significantly increased by the gel, but was not disturbed by either the mouthwash or the NaF. Cell proliferation determined by MTT decreased significantly only for the NaF-treated samples; protein content assay experiments showed no Such effect. This study indicates that epithelial cell culturing results can depend on the method used, and the adverse effects of a high F- concentration and low pH should be considered when prophylactic gels are applied by patients with Ti implants or other dental devices. (c) 2008 Wiley Periodicals, Inc.